How to use the Pelvic Organ Prolapse Quantification (POP‐Q) system?. (15th August 2018) - Madhu, Chendrimada; Swift, Steven; Moloney‐Geany, Sophie; Drake, Marcus J.
Abstract : Aims: To set out the basic description of pelvic organ prolapse (POP) using the International Continence Society/International Urogynecology Association Pelvic Organ Prolapse Quantification (POP‐Q) system. Methods: The basic approach to use of the POP‐Q was identified and summarized. Results: Six defined points in the vagina are identified; points Aa and Ba for the anterior vagina, Ap and Bp for the posterior vagina, and C and D for the cervix/vault. Point D is not used in women who previously had a hysterectomy. The patient is asked to strain, ideally when in the standing position, to elicit the POP to its maximum extent. The location of the defined points is then gauged relative to the hymenal ring and recorded on a grid. Three additional measurements are taken to achieve a full description; the genital hiatus length, perineal body length, and total vaginal length. Staging a POP relies on identifying the lowest extent of any part of the six defined points; if any point reaches close to the hymenal ring (at least stage 2), the prolapse is usually symptomatic. Conclusions: The POP‐Q system is readily cataloged and offers detailed description of considerable benefit in clinical practice and research.